Driving Competitive Edge in Sarawak's Manufacturing Industry: Leveraging Supply Chain Management, Smart Integration, and Circular Economy Practices - Kouk Ping Jap (Recoletos Multidisciplinary Research Journal)
Sarawak's manufacturing industry is vital to the state's economy, contributing to employment, GDP, and overall development. The industry must enhance supply chain management, integrate smart solutions, and adopt circular economy principles to stay globally competitive. Effective flow control of materials, information, and finances is essential for operational excellence and market adaptability. Key technologies like AI, blockchain, and IoT should be adopted to create faster, cost-efficient, customer-centric processes and products. Emphasizing resource, material, and waste reduction aligns with circular economy goals, reducing costs and fostering long-term growth. This review merges academic research with practical insights, offering actionable strategies for policymakers, industry players, and scholars to drive sustainable innovation in Sarawak's industrial landscape.